0422 Apocalypse Tau: The Relationship Between Inflammaging and Local Sleep Disruption in Older Adults is Mediated by Tau Burden. (27th May 2020) - Dave, A; Sprecher, K E; Lui, K K; Chappel-Farley, M G; Chen, I Y; Blennow, K; Zetterberg, H; Riedner, B A; Bendlin, B B; Mander, B A; Benca, R M
Abstract: Introduction: Chronic inflammation in aging is independently associated with tau burden and sleep disruption, though the mechanism linking inflammation with sleep disruption remains unknown. Recent evidence associates tau burden with deficits in local expression of sleep spindles and slow wave activity (SWA). Here we test the hypothesis that age-related central inflammation disrupts local sleep by influencing tau pathology. Methods: Cognitively asymptomatic older adults from the Wisconsin Alzheimer's Disease Research Center underwent overnight polysomnography with high-density electroencephalography (hdEEG; 256 channels) at the University of Wisconsin-Madison (n=33, 61.9±6.7 years, 23 female). EEG data were subjected to multitaper spectral analysis (0.5-40Hz) to yield topographic maps of SWA (SWA1:0.5-1Hz, SWA2:1-4.5Hz) and spindle (sigma1:11-13Hz; sigma2:13-16Hz) power during NREM sleep. Cerebrospinal fluid assay-based measurements of YKL-40 (indicating glial activation), phosphorylated tau (Ptau ), and total tau (Ttau ), were correlated with SWA and sigma topographical power employing Holm-Bonferroni correction. Multiple linear regression models were implemented controlling for age, apnea-hypopnea index (AHI), and sex at significant derivations. Finally, Sobel testing was employed to assess whether tau burden mediated YKL-40-sleep associations. Results: Age was associated with YKL-40 (r=0.53, p=0.002), and YKL-40 was associated with both Ptau (r=0.66, p<0.001) and Ttau (r=0.68, p<0.001). Correlations between sigma2 activity and both Ptau and Ttau were detected at 14 derivations, 12 of which remained significant after controlling for age, sex, and AHI. YKL-40 was associated with sigma2 power (r=-0.39, p=0.025) across derivations expressing peak significance with tau. Sobel mediation analyses indicated that both Ptau (t=-2.15, p=0.031) and Ttau (t=-2.36, p=0.018) mediated the relationship between YKL-40 and sigma2 activity at these derivations. SWA was not associated with Ttau, Ptau, or YKL-40. Conclusion: These results suggest that age-related increases in central glial activation may disrupt local expression of fast spindles by increasing tau burden, highlighting a potential role for chronic inflammation in sleep deficits observed in aging and Alzheimer's disease. Support: Supported by R56 AG052698, P50AG033514